Identification Of Bilinear Systems With Emphasis On Dynamic Modelling Approaches - Timothy, Yap Tzen Vuin (2005)
Bilinear systems are nonlinear systems which are commonly found in industry. Examples include heat transfer processes, chemical reactor systems and paper machines. As such, it is of interest to analyse these systems particularly in terms of the effects of nonlinearity on the underlying linear dynamics. This is achieved by obtaining the approximate linear model known as the related linear dynamic model, using crosscorrelation analysis. The nonlinear distortions present are investigated, for different input signals, namely maximum length binary, maximum length ternary and multisine signals.